Substantive Bias and Natural Classes An Empirical Approach - Lin, Yu-Leng (Frontiers in Chinese Linguistics, 2019)
This book offers a laboratory phonological analysis of the sonority hierarchy and natural classes in nasal harmony using an artificial grammar-learning paradigm. It is aimed at postgraduate students and linguists in general whose research interests lie in phonology, phonetics, and/or psycholinguistics. It is useful for linguists who are struggling to figure out how to effectively design an artificial phonological grammar and those who have not designed experiments on their own but would like to do so as an additional means to testing linguistic theories. This book is also a valuable resource for anyone building crosslinguistic artificial grammar paradigm resources.